Pengaruh Pengendalian Intern Perkreditan Terhadap Kredit Bermasalah Pada PT. Bank Rakyat Indonesia (Persero) TBK, Cabang Teluk Betung - Haninun HANINUN (Universitas Bandar Lampung (UBL), 2011)
Development bank in Lampung province experienced a fairly rapid developments, this rapid growth led to increased competition among banks in seizing the customer to raise funds as much as possible from the community. Funds raised are then arranged in order to provide benefits for banks, in other words, the funds channeled back into the community in the form of credit. Bank as a form of business entity, of course activities undertaken expect profit. It is a natural thing, but in the implementation of the provision of credit, in addition to fulfilling the objectives of banking business motive profile bank also should serve as an agent of development, meaning that the bank should be able to guide the debiturny, so that the loan has been disbursed to meet the original target. To maintain the position of overseeing monetary and credit can be done by setting the direction of credit such as credit type setting priorities as has been done by PT. Bank Rakyat Indonesia. (Persero) Tbk. Teluk Betung branch. This type of research in the form of descriptive research and associative. Descriptive research conducted to get an overview of the variables used in this study, whereas associative research is used to examine the relationship between internal control or influence of the level of over due loans credit by using statistical test.